Efektifitas Edukasi Gizi Melalui Media Booklet Tentang Pemberian Makanan Tambahan (PMT) Pada Balita Wasting - Nathasa Weisdania Sihite; Manuntun Rotua; Ayu Cintiya; Ridhotun Annisa; Omega Tri Grese (Unika Santu Paulus Ruteng, 2023)
Wasting is a nutritional problem that often occurs in Indonesia. Handling the problem of wasting can be done in many ways, one of which is to carry out nutrition education that is right on target. Community service activities aim to provide knowledge about the effectiveness of supplementary feeding (PMT) in dealing with wasting problems in the form of educational media, namely the pocketbook